Influence of intensified motor activity on somatic development of boys aged 12-15 years - Gołębiowska, Maria; Grabowska, Jadwiga; Becker, Mieczysław; Chlebna-Sokół, Danuta (Anthropological Review, 1978)
Material for this study comprises anthropometric data collected longitudinaly over period of 3 years. Observations were reperated every 6 months on a group of 118 boys aged 12,5 - 15,0 years selected from 6 schools of the city of Łódź. Subjects were divided into two groups: experimental (E) and control (K). Group E, encompassed 59 boys subjected to extended program of physical education. Control group of the same size comprised boys from classes with standard physical education program. Anthropometric characteristics studied were: body height, trunk length, lengths of extremities, shoulder breadth, hip breadth, body weight and three skinfolds. Lean body mass was ascertained from Pafizkova nomogram, phases of secondary and tertiary sexual characters were assesed with the aid of 5-grades Tanner's scale. It has been found that, as an effect of increased motor activity, members of E group had accelearted sexual maturation, increased sizes of analysed characters and raised rate of their growth.